2004
DOI: 10.1038/sj.bjc.6601660
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunohistochemical method for estimating cell cycle phase distribution in ovarian serous neoplasms: implications for the histopathological assessment of paraffin-embedded specimens

Abstract: We have investigated whether immunohistochemical markers can identify differences in cell cycle phase distribution in ovarian serous neoplasms, including borderline tumours of different grades. Sections of normal ovary (n ¼ 18), serous cystadenoma (n ¼ 21), borderline serous tumours (n ¼ 21) and serous cystadenocarcinoma (n ¼ 15) were analysed by immunohistochemistry using markers of cell cycle entry (Mcm-2) and cell cycle phase, including cyclin D1 (mid-to-late G1), cyclin A (S phase), cyclin B1 (G2 phase) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…However, our overall technique has previously been validated in surgical resection specimens of colorectal carcinoma and ovarian neoplasms, in which we showed that our immunohistochemical model resulted in comparable cell cycle phase analyses to those obtained by flow cytometry Scott et al, 2004). Nevertheless, confirmation of these observations by parallel flow cytometric and immunohistochemical analysis of laryngeal tumours will be important before commencing appropriately powered prognostic/predictive studies of larger numbers of samples.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, our overall technique has previously been validated in surgical resection specimens of colorectal carcinoma and ovarian neoplasms, in which we showed that our immunohistochemical model resulted in comparable cell cycle phase analyses to those obtained by flow cytometry Scott et al, 2004). Nevertheless, confirmation of these observations by parallel flow cytometric and immunohistochemical analysis of laryngeal tumours will be important before commencing appropriately powered prognostic/predictive studies of larger numbers of samples.…”
Section: Discussionmentioning
confidence: 62%
“…Minichromosome maintenance protein 2 is one of six MCM proteins (MCMs 2 -7) that assemble in the prereplication complex and are essential for DNA replication in eukaryotic cells (Kearsey and Labib, 1998 six proteins are abundant throughout the cell cycle but are broken down rapidly on differentiation and more slowly in quiescence (Musahl et al, 1998). Antibodies against Mcm-2 have previously been shown to detect more cycling cells in laryngeal tissues than other 'proliferation' markers such as Ki67 (Chatrath et al, 2003), and immunohistochemical staining for Mcm-2 and/or Mcm-5 has been shown to be of value in identifying malignant or premalignant lesions in a range of clinical specimens (Williams et al, 1998;Freeman et al, 1999;Davies et al, 2002;Going et al, 2002;Chatrath et al, 2003;Scott et al, 2003;Sirieix et al, 2003;Scott et al, 2004).…”
mentioning
confidence: 99%
“…With the development of (Meng et al, 2001;Padmanabhan et al, 2004) and ovarian serous neoplasms (Scott et al, 2004) chondrosarcoma (Helfenstein et al, 2004), oligodendroglial tumours (Wharton et al, 2001(Wharton et al, , 2004, oesophageal neoplasm (Going et al, 2002), renal cell carcinoma (Dudderidge et al, 2005), breast cancer (Gonzalez et al, 2004), endometrial carcinoma (Li et al, 2005) and thyroid carcinoma (Guida et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies focused on the detection of MCM2 (Freeman et al, 1999;Chatrath et al, 2003;Davidson et al, 2003;Kodani et al, 2003;Scott et al, 2004). So far only few investigations studied MCM6 expression (Labib et al, 2001;Helfenstein et al, 2004).…”
mentioning
confidence: 99%
“…Thus, immunodetection of phosphohistone H3 has become a sensitive and specific marker of mitotic figures and correlates with outcome in a variety of different human tumor types, 9 including breast carcinoma, 10,11 colorectal adenocarcinoma, 12 ovarian serous adenocarcinoma, 13 pulmonary neuroendocrine carcinoma, 14 uterine smooth muscle tumors, 15 astrocytomas, 16 and meningiomas. 17 In melanoma, immunodetection of phosphohistone H3 has been shown to increase the sensitivity and accuracy for mitotic figure detection; it improves inter-observer variability; and it reduces the time required to identify mitoses in primary cutaneous and uveal melanomas.…”
mentioning
confidence: 99%